4D-printed bilayer hydrogel with adjustable bending degree for enteroatmospheric fistula closure. (December 2022) - Qu, Guiwen; Huang, Jinjian; Li, Ze; Jiang, Yungang; Liu, Ye; Chen, Kang; Xu, Ziyan; Zhao, Yun; Gu, Guosheng; Wu, Xiuwen; Ren, Jianan
Abstract: Recently, four-dimensional (4D) shape-morphing structures, which can dynamically change shape over time, have attracted much attention in biomedical manufacturing. The 4D printing has the capacity to fabricate dynamic construction conforming to the natural bending of biological tissues, superior to other manufacturing techniques. In this study, we presented a multi-responsive, flexible, and biocompatible 4D-printed bilayer hydrogel based on acrylamide-acrylic acid/cellulose nanocrystal (AAm-AAc/CNC) network. The first layer was first stretched and then formed reversible coordination with Fe 3+ to maintain this pre-stretched length; it was later combined with a second layer. The deformation process was actuated by the reduction of Fe 3+ to Fe 2+ in the first layer which restored it to its initial length. The deformation condition was to immerse the 4D construct in sodium lactate (LA-Na) and then expose it to ultraviolet (UV) light until maximal deformation was realized. The bending degree of this 4D construct can be programmed by modifying the pre-stretched lengths of the first layer. We explored various deformation steps in simple and complex constructs to verify that the 4D bilayer hydrogel can mimic the curved morphology of the intestines. The bilayer hydrogel can also curve in deionized water due to anisotropic volume change yet the response time and maximum bending degree was inferior to deformation in LA-Na and UV light. Finally, we made a 4D-printed bilayer hydrogel stent to test its closure effect for enteroatmospheric fistulas (EAFs) in vitro and in vivo . The results illustrate that the hydrogel plays a role in the temporary closure of EAFs. This study offers an effective method to produce curved structures and expands the potential applications of 4D printing in biomedical fields. Graphical abstract: Image 1 Highlights: A novel strategy to fabricate 4D-printed multi-responsive bilayer hydrogels is proposed. The deformation mechanism relies on shrinkage anisotropy between two layers in lactate sodium solution and ultraviolet. The 4D shape-morphing hydrogel can adapt to intestinal curvature for enteroatmospheric fistula closure.